Classification of Aedes Adults Mosquitoes in Two Distinct Groups Based on Fisher Linear Discriminant Analysis and FZOARO Techniques - Okwonu, Friday Zinzendoff; Dieng, Hamady; Abdul Rahman, Othman; Hui, Ooi Seow (International Institute for Science, Technology and Education, 2012)
This paper describes the breeding, feeding and measurement of Aedes mosquitoes based on body size (wing length). Due to similarity in body size measurements, we were constrained on gender recognition. To reveal the gender identity of these mosquitoes, Fisher linear discriminant analysis and FZOARO classification models were considered suitable for prediction and classification. We randomly selected 15 mosquitoes from each groups and categorize the body size as small and large and applied the classification procedures. Both classification techniques perform similar. The numerical simulation reveals that 86.67% were classified as male for group one and 80% were correctly classified as female in group two.